Prototipo de exploración educativa basada en realidad mixta para cirugía con casco Meta 2 - Aguilar, Eliana; Solarte Correa, Pedro Luis; Dorado, Jesus Humberto; Sabater, José María; Vivas Albán, Oscar Andrés (Ingeniería, 2022)
Context: This article describes an educational or pre-surgical mixed-reality prototype using the Metavision Meta II headset. 3D objects of morphological structures for neurosurgery and laparoscopy were created from MRI and CT images of a real patient in order to simulate the access to the brain and conduct a reconnaissance of the abdominal area. Method: This prototype has an educational approach whose objective is to encourage the recognition of morphological schemes of organs, for which three tests were designed. These tests consisted of searching for tumors through navigation and interaction with an object displayed in the Meta 2 mixed-reality headset. Two of the three tests were dedicated to the neurological area, in which the search time was measured with five tumors, and a test was conducted for the abdominal area regarding the search of two tumors, designing various interactions in the spatial path of the generated 3D object. An immersion measurement process was conducted which was based on the use of a questionnaire. Results: 100% of users found the application highly interesting, while 90% expressed that they tried to focus their attention on the successful completion of the test, an indicator of the level of absorption of the application. Furthermore, 70% of users described their experience as highly immersive. Conclusions: Tests showed the prototype to be usable, absorbent, and has an acceptable level of immersion.